Concrete at high temperatures: a case study of a fire in a residential building in Minas Gerais (Research, Society and Development, 2021)
This paper deals with a structural diagnosis carried out in the Afonso Alves Residential Building, in Barbacena, Minas Gerais, after the occurrence of a fire that damaged all the reinforced concrete structures. First, a bibliographic review was made on the behavior of concrete when submitted to high temperatures, explaining the main physical and chemical phenomena that occur in this condition and discussing the effects observed from the concrete microstructure to a macroscopic analysis. Besides, it was discussed the reactions that are triggered when the hardened reinforced concrete is undergoing the process of temperature increase, reaching high temperatures and also when it suffers the cooling process. The main pathologies found in reinforced concrete structures, their main causes, effects and ways to prevent them were presented, to preserve the useful life foreseen in the project's conception. It was also highlighted the extreme importance of the Fire and Panic Prevention and Combat Project in buildings, whether residential, commercial or industrial. Next, the description of the studied building was made, presenting the structural diagnosis in a detailed way, indicating the main structures affected by the fire, the visual inspections in all the visible structures and the results of the destructive and non-destructive tests. Finally, some recovery measures were pointed out that should be adopted to treat the pathologies that are compromising the stability and durability of the reinforced concrete structures, besides recommending some structural reinforcements, to guarantee the safety of the building and its occupants.